2007
DOI: 10.1128/jvi.02320-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Infection of Human CD4 + T Cells by Microbial HSP70 and the Peptide Epitope 407-426

Abstract: Targeting the cognate human immunodeficiency virus type 1 (HIV-1) antigen is the classical way of preventing HIV-1 infection, but this approach has encountered serious problems in eliciting effective cytotoxic T lymphocytes (CTL) and neutralizing antibodies. Both CTL and neutralizing antibodies are subject to viral escape, and HIV-1 mutation may occur in the acute (30), as well as the chronic, phase of infection (4,12,15). Indeed, HIV-1 sequences found in a population may represent largely CTL escape variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…2c; Wang et al 2005a, b). Furthermore, the dose-dependent inhibition of HIV-1 infection of human CD4 + T cell lines by Hsp70 has been reproduced by p407-426 (Babaahmady et al 2007). The mechanism involves the stimulation of CCL-3, CCL-4 and CCL-5 chemokines, which bind and down-modulate CCR5, thereby preventing HIV-1 binding to the CCR5 co-receptors.…”
Section: Tuberculosis Hsp70 and Host Immunity (Tl)mentioning
confidence: 82%
See 2 more Smart Citations
“…2c; Wang et al 2005a, b). Furthermore, the dose-dependent inhibition of HIV-1 infection of human CD4 + T cell lines by Hsp70 has been reproduced by p407-426 (Babaahmady et al 2007). The mechanism involves the stimulation of CCL-3, CCL-4 and CCL-5 chemokines, which bind and down-modulate CCR5, thereby preventing HIV-1 binding to the CCR5 co-receptors.…”
Section: Tuberculosis Hsp70 and Host Immunity (Tl)mentioning
confidence: 82%
“…A comparative experiment in which GFP-labelled pseudovirions are treated with Hsp70, and LPS showed that the LPS-treated cells were 5-to 6-fold higher than Hsp70-treated counterparts. Hsp70 also increased A3G expression in CD8 + and CD4 + T cells and DCs to a greater extent than LPS, and LPS had no detectable effect on A3G expression at concentrations of 2.5 to 20 ng/ml (Babaahmady et al 2007). The Janus-like properties of HSPC4 (gp96) (A.G.P.…”
Section: Tuberculosis Hsp70 and Host Immunity (Tl)mentioning
confidence: 99%
See 1 more Smart Citation
“…HSP70 also functions as a coadjuvant by virtue of binding among other receptors, CD40 and the CCR5 molecules, and Toll-like receptor 4 (TLR4) in dendritic cells (DCs) and macrophages (14,(17)(18)(19). Furthermore, microbial HSP70 inhibits in vitro HIV-1 infection of human CD4 ϩ T cells (20). Thus, HSP70 may function as a coadjuvant, enhancing innate immunity, and when linked to antigen it may induce adaptive immune responses.…”
Section: Vaginal Immunization Of Women With a Vaccine Consisting Of Hmentioning
confidence: 99%
“…It is therefore important to note that M. tuberculosis Hsp70 can dosedependently inhibit the infection of CD4 T cells by HIV-1, the active site in this protein being the C-terminal epitope 407-426. The Hsp70 apparently works by blocking the CCR5 co-receptor and by inhibition of CC-chemokines (Babaahmady et al 2007). This suggests a therapeutic potential for this protein and a re-examination of the M. tuberculosis/HIV-1 relationship.…”
Section: Hsp60mentioning
confidence: 99%